Are Academic Libraries Doing Enough to Support the Sustainable Development Goals (SDGs)? A Mixed-Methods Review - Dabengwa, Israel Mbekezeli (Evidence Based Library and Information Practice, 2025)
Objective – The goal of this study was to assess global academic libraries' role and activities aimed at achieving Sustainable Development Goals (SDGs). The paper highlights the enablers and barriers encountered in SDG programming and identifies future directions of SDG research in academic and other types of libraries.Methods – A mixed-methods review was conducted to address the research question: How do academic libraries contribute to the attainment of SDGs? The methodology included literature searches conducted in Scopus, Web of Science Core Collection, EBSCO’s Library, Information Science & Technology Abstracts (LISTA), and hand-searching. The selected timeframe, 2017-2024, encompasses the introduction of the SDGs and extends to the present body of evidence.Results – The study found 25 relevant articles with data from 164 academic libraries worldwide. The evidence base indicates limited awareness and examples of sustainability literacy, suggesting the need for new initiatives. Instances of "SDG washing" were identified where librarians exaggerated the impact of their SDG-related programs, mislabeled routine activities as SDG contributions, or used SDG terminology superficially without meaningful action. This study suggests that SDG attainment is influenced by leadership, organizational culture, personal initiatives, and partnerships.Conclusions – Academic libraries simultaneously address multiple SDG targets, indicating a comprehensive sustainability approach. Positive correlations between specific targets imply synergies that libraries can exploit to strengthen their sustainable development roles. Future research should investigate the impact of institutional factors on SDG implementation in academic libraries and identify strategies to overcome the common challenges in SDG initiatives. Specific SDG targets and indicators should guide context-specific recommendations. It is also advised to develop standardized tools for measuring and comparing academic libraries' SDG contributions.